Analisis Sensitivitas Model Linear Programming Untuk Optimalisasi Produksi Pia Cendana Menggunakan Metode Branch and Bound - Novarianti Firdaus; Salmun K. Nasib; Djihad Wungguli (Scimadly Publishing, 2025)
This study aims to optimize the production of Pia Cendana enterprise using a linear programming model based on the Branch and Bound method. In order to achieve maximum profit, a mathematical formulation is constructed, including an objective function and constraint functions based on data regarding raw material composition, resource availability, production costs, and selling prices of each product variant. The Branch and Bound method was applied to obtain an optimal solution in the form of integers that are operationally valid. In addition, a sensitivity analysis was conducted to evaluate the impact of changes in coefficients within the objective function and constraints on the optimal solution. The findings show that the Pia Cendana enterprise can achieve an optimal profit of IDR 1,620,000 or 1.86 % per month. This amount is higher than the previous actual profit of only IDR 86,888,000, indicating a profit increase of IDR 88,508,000. The study indicates that this method improves resource efficiency and yields more profitable production. The optimal solution demonstrates that production can be increased while still considering capacity and raw material limitations. The sensitivity analysis also proves that the model is sufficiently stable against parameter variations. This study provides practical contributions to Pia Cendana enterprise in formulating more efficient and profitable production strategies.